The Role of Systemic Functional Grammar in the Expansion of Nominal Groups - María Claudia Nieto Cruz (Universidad Nacional de Colombia, 2019)
This study presents the expansion of nominal groups in a systemic functional grammar class of an English language teacher program in 2016 at a Colombian public university. The participants were six student teachers. Nominal groups were first considered in a document written by the students before being exposed to the principles of systemic functional grammar and then in a revised version after the exposure to it. The study shows initial improvements in the enlargement of nominal groups between the two written productions and provides insights into the enormous potential for structural and meaningful expansion and the complexity of nominal groups. The gained awareness may become a cognitive framework for students to produce complex nominal groups in academic productions demanded in their studies and in the exercise of their professional practice.